Evaluating Suppliers/Consultants and Procuring Entities in the landscape of Public Procurement in Bangladesh - Md. Shahidul Islam (International Journal of Supply Chain Management, 2017)
Promoting good corporate governance to the business community (suppliers/ consultants) and procuring entities in order to build professionalism about procurement issues is a latest challenge in the field of Public Procurement in Bangladesh. This paper discusses on application of Public Procurement Rules to develop a transparent, accountable and efficient procurement for better overall value for money and sustainable development of all sectors of the Government of Bangladesh. The purpose of this study is to identify various implementation bottlenecks to the Public Procurement in Bangladesh.